Financial Management in Agri business: Capital Optimization and profitability - Leny Yuliyani; Betty Rofatin; Tedi Hartoyo (Maneggio, 2025)
This study examines the role of financial management in agribusiness business with a focus on capital optimization and increased profitability. Through the Systematic Literature Review (SLR) method of a number of articles and journals published between 2020 and 2025, it was found that effective capital management, including working capital planning, cost control, and appropriate resource allocation, are key factors in supporting the continuity and growth of agribusiness businesses. In addition, there is a significant positive relationship between capital optimization and profitability, where business actors who implement adaptive and data-driven financial strategies obtain higher profit margins. The research also revealed that access to external financing plays an important role in supporting capital optimization, even though small and medium-scale agribusiness actors still face various obstacles in accessing such financing. The use of information technology and digital financial management systems is a strategic solution to improve the accuracy of financial recording and decision-making quickly and precisely. These findings underscore the need to develop professional and integrated financial management capacity to increase the profitability and competitiveness of agribusiness businesses in the digital era. This research provides the basis for the development of financial management models and strategies that are applicable in the agribusiness sector.